Sociology of Sponsorship Health Controversy In The Sports Industry - Eric Mayo Dagradi; Noortje Anita Kumaat; Himawan Wismanadi; Bella Shasi Saraswara; Asami Rietta Kumala (UNIVERSITAS NEGERI MAKASSAR, 2024)
Sponsorship in sports is very important because it allows the development of athletes, and teams, and has a major impact on the economy. Sponsorship allows companies to align themselves with the values, emotions, and excitement of sports. Types of sports sponsorship include event sponsorship, team sponsorship, and athlete sponsorship. In Indonesia, cigarette sponsorship in sports is still a topic of debate because it is related to social, economic, health, and cultural aspects. Cigarette sponsorship in sports also raises a contradiction between the message conveyed by sports and the negative health impacts caused by smoking. Sociological analysis is very important to understand the impact and implications of sports sponsorship by cigarette companies.